Exploring Wonder in Medical School Admissions: Correlations with Admissions Decisions - Eojin Choi; Maria W. Merritt; Gail Geller (International Journal of Medical Students)
Background:The capacity for wonder (CfW), which has been proposed as an important personal disposition for clinicians, may provide a meaningful picture of medical school applicants. The purpose of our study was to explore experiences of wonder among applicants and their association with components of the admissions process.